SAE Technical Paper Series 1993
DOI: 10.4271/931136
|View full text |Cite
|
Sign up to set email alerts
|

Use of Infra-Red Thermography for Automotive Climate Control Analysis

Abstract: greatest possiblethermal resolution, in most systems, the sensorconsistsof a singleinfra-reddetector(suchas In this paper, several automotive climate control mercury/oadmlum/telluride). Electromechanicalservos applications for IR thermographyare described. Some of (galvanometers)oscillate mirrors to perform horizontal these applicationscan be performed usingconventional and verticalscanningof the image ontothe detector.The IR techniques. Others, such as visualizing the air detector respondsto the sum of the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The Infrared thermography is non-invasive, non contact imaging approach that has been proposed by certain authors to measure the temperature variation on the human skin temperature [25,122,123]. As shown by Alahmer et al [3], using infrared thermography is possible to achieve real-time measurements of solid surfaces temperature fields within the vehicular cabin in addition to clothes and visible body parts of the human subjects.…”
Section: Prediction Of the Vehicular Comfort State Using Infrared Thementioning
confidence: 99%
See 1 more Smart Citation
“…The Infrared thermography is non-invasive, non contact imaging approach that has been proposed by certain authors to measure the temperature variation on the human skin temperature [25,122,123]. As shown by Alahmer et al [3], using infrared thermography is possible to achieve real-time measurements of solid surfaces temperature fields within the vehicular cabin in addition to clothes and visible body parts of the human subjects.…”
Section: Prediction Of the Vehicular Comfort State Using Infrared Thementioning
confidence: 99%
“…There is a limited number of papers in the literature discussing the use of infrared thermography to measure and evaluate the thermal conditions inside the cabin, even though this optical technique seems to be a promising tool in the assessment of the comfort state in vehicular cabins, given that the surface's temperature is one of the most influencing parameters in this case. An early study of Burch et al [122] displays several automotive applications of infrared thermography with focus on its use for automotive climatic control analysis. The author proposes a method for measuring ambient air temperature by using a thin (0.15 mm) layer of polyethylene plastic mounted perpendicular to the air stream.…”
Section: Prediction Of the Vehicular Comfort State Using Infrared Thementioning
confidence: 99%
“…By inserting a high emissivity mesh into the flow (e.g. Anderson et al [2], Burch et al [3]), IRT can be used to measure temperature distributions in flow fields. In the past, different materials, such as paper screens, have been used (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that period in this case. This method had previously ventilation would bring the seat temperature to that been proposed by Burch et al [35] in 1993 for of the ambient and increase the thermal comfort of other automotive applications. The results were the passenger.…”
Section: Introductionmentioning
confidence: 99%